The e-hate speech in jordan - Ali O. Nejadat, Khalaf M. Tahat, Zuhair Y. Tahat, (Opción, 2019)
The aim of this study is to know the extent to which Jordanians are aware of the concept of hate speech on social media based on the survey methodology. The results of the study revealed that there was a high level of understanding of the concept of hate speech, with about (73%) defining the concept of hate speech and related definitions and forms. In conclusion, the more the respondents are capable of identifying the concept of hate speech, the greater their ability to perceive its effects on society it was accepted by the results.